Reliability of lab-on-a-chip technologies for wearable electronics: a perspective - Subudhi, Swarup Kumar; Das, Siddhartha (Frontiers in Sensors, 2023)
Over the past few decades, Lab-on-a-chip (LoC) devices have made health diagnostics easier and cheaper by enabling rapid, hassle-free, and inexpensive measurements of different biochemical markers, properties of epidermally retrievable biofluids (e.g., sweat and interstitial fluids), etc. The miniaturization of these sensing technologies along with the integration of flexible frameworks (microfluidic assemblies and electronics) and user-friendly software have paved the way for autonomous and continuous tracking of human health parameters. However, with emerging new technologies, there are new and complex challenges, especially in the case of these miniature LoC devices. Although microfluidics-specific challenges such as analyte contamination, flow rate variability, improving detection specificity, etc. are being worked upon, the bigger question is: how reliable are these wearable devices in the long run? This perspective piece initially talks about the state-of-the-art LoC technologies that have been incorporated into wearable devices. Next, the perspective identifies some of the reliability studies conducted (as well as overlooked) on the integrated wearable electronics used. Finally, the paper discusses the challenges and future directions of research in the field of reliability of LoC-based wearable electronics.